Relation between in-game role and service characteristics in elite women's volleyball - Quiroga, M. E.; Garcia-Manso, J. M.; Rodriguez-Ruiz, D.; Sarmiento, S.; de Saa, Y.; Moreno, M. P. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to determine whether the in-game role of players (setter, outside, middle, or opposite player) in elite women's volleyball is significantly related to the characteristics of their service. The sample consisted of 1,300 service deliveries (total serves for all matches) made by players in the 8 teams participating in 2 Final 4 stages of the Indesit European Champions League. The variables recorded were in-game role of the server, service type, speed of delivery, service area, target zone, and effectiveness of delivery. Results showed a significant relation between the server's in-game role and service type (p = 0.01), service speed (p = 0.01), service area (p = 0.01), and effectiveness of delivery (p = 0.001). The most significant relation observed was with the service area, primarily because of the server having to make a quick transition to the defense zone. Setters and opposite players most commonly served from behind zone 1 (100 and 80% of serves, respectively), which they defended after serving. Similarly, middle players served most frequently from behind zone 5 (47% of serves), the zone they subsequently defended.